2013
DOI: 10.1111/een.12020
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea aphid (Aphis craccivora) associated with different host plants has different facultative endosymbionts

Abstract: Maternally inherited facultative endosymbiotic bacteria are common among insects, including many polyphagous insect herbivores. To investigate whether symbiont infection is structured by host plant in the polyphagous aphid Aphis craccivora Koch, pyrosequencing and diagnostic PCR were performed on 26 populations from two different host plants, alfalfa (Medicago sativa) or black locust (Robinia pseudoacacia). Results indicated that Aphis craccivora harbours distinctly different microbial communities in alfalfa v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 25 publications
7
97
0
Order By: Relevance
“…craccivora is infected with the heritable facultative symbiont H. defensa, which confers protection against some species of parasitic wasps (37,38). Despite clear benefits to infection in the presence of wasps, however, this symbiont is found only at intermediate frequencies in natural populations (44,45). In this study, we identified clear costs to infection and maternal transmission failures associated with this protective symbiont, which likely constrain H. defensa spread in natural populations.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…craccivora is infected with the heritable facultative symbiont H. defensa, which confers protection against some species of parasitic wasps (37,38). Despite clear benefits to infection in the presence of wasps, however, this symbiont is found only at intermediate frequencies in natural populations (44,45). In this study, we identified clear costs to infection and maternal transmission failures associated with this protective symbiont, which likely constrain H. defensa spread in natural populations.…”
Section: Discussionmentioning
confidence: 75%
“…craccivora as factors constraining the spread of this symbiont in natural populations, given that this symbiont confers protection against parasitoids (37) yet remains at intermediate frequencies (0 to 85%) in natural populations (44,45). In addition, we sought to characterize certain attributes of H. defensa infecting Ap.…”
mentioning
confidence: 99%
“…Also, the conditions that favor the maintenance of certain symbionts in the field may be absent in the lab, such as removal of natural enemies in the case of defensive symbionts [55]. Clearly, one of the main differences in the rearing conditions that the mealybugs encountered in this study is host plant, which is a common determinant of symbiont communities in herbivorous insects [4]. For example, in Acyrthosiphon pisum (Hemiptera: Aphididae) pea aphids, infection with specific bacterial endosymbionts is repeatedly associated with successful colonization of specific host plants [30].…”
Section: Discussionmentioning
confidence: 99%
“…We screened the aphid clones for common aphid endosymbionts using (i) symbiont‐specific diagnostic PCR for all known A. craccivora symbionts and (ii) denaturing gradient gel electrophoresis (DGGE) following amplification of a variable region of 16S rRNA to detect any unexpected symbionts. Diagnostic PCR was conducted using previously published primers and protocols (Brady & White ; Brady et al . ) following a 10% w/v Chelex DNA extraction (Wulff et al .…”
Section: Methodsmentioning
confidence: 99%
“…Here, we investigate the role of facultative symbionts in the dietary breath in Aphis craccivora Koch (cowpea aphid). We previously reported a strong correlation between particular facultative symbionts and food plant use in A. craccivora (Brady & White ; Brady et al . ), a polyphagous aphid with a cosmopolitan distribution (Blackman & Eastop ).…”
Section: Introductionmentioning
confidence: 99%